Dietary Behaviors Associated With Fruit and Vegetable Consumption, Marion County, Indiana, 2005 - Karl W. Staser; Terrell W. Zollinger, DrPH; Robert M. Saywell Jr, PhD, MPH; Srujana Kunapareddy, MPH; P. Joseph Gibson, PhD; Virginia A. Caine, MD (Centers for Disease Control and Prevention, 2011)
IntroductionEating inadequate amounts of fruits and vegetables is associated with diminished health, and most Americans fall short of the Centers for Disease Control and Prevention's recommendation to eat at least 2 servings of fruit and 3 servings of vegetables each day. This study assessed behaviors associated with fruit and vegetable consumption in adults.MethodsA cross-sectional, random-digit-dialed telephone survey of 4,784 adults living in Marion County (Indianapolis), Indiana, measured demographic characteristics, personal health data, food consumption, food label use, and other eating habits. Multivariate logistic regressions were used to assess the association between selected dietary behaviors and fruit and vegetable consumption, controlling for demographic characteristics.ResultsBehaviors associated with adequate versus inadequate consumption of fruits and vegetables were frequent snacking on healthy foods (odds ratio [OR], 2.54), eating meals at home (OR, 2.09), using nutrition labels when making purchases (OR, 1.52), and using "heart healthy" symbols and other food information labels when ordering from restaurants (OR, 1.41). Frequent red meat consumption was negatively associated with adequate consumption of fruits and vegetables (OR, 0.64).ConclusionsHealthful snacking, food label use, and eating meals prepared at home may improve dietary quality. Our measure of adequacy may also be useful in future studies assessing dietary behavior and diet composition.